Public attitudes towards "pest" management: Perceptions on squirrel management strategies in the UK. (June 2018) - Dunn, Mike; Marzano, Mariella; Forster, Jack; Gill, Robin M.A.
Abstract: The impacts of non-native, invasive grey squirrels ( Sciurus carolinensis ) on broadleaf woodlands and red squirrel population ( Sciurus vulgaris ) are well recognised among wildlife professionals, yet efforts to control the species across its expanding range require substantial time and resources. Through collaboration, wildlife professionals and communities can more effectively implement the population monitoring and control programmes necessary to conserve native species under threat. However, for such collaboration to be successful, wildlife professionals must first understand public attitudes towards grey squirrels, and the control methods available. Through a national level survey ( n  = 3758) we examine the UK public's attitudes to red and grey squirrels, and the acceptability of seven control methods. Results show that much of the public have little knowledge of the grey squirrel's negative impacts. In fact, contrary to the notion of a pest species, the presence of grey squirrels is often desirable. Furthermore, those control methods recommended by wildlife professionals are regarded by the public as some of the least acceptable. Those most accepting of controls include males, older generations, those most knowledgeable about squirrels and people who are aware of squirrel management being practiced in their local area. To foster more fruitful collaboration, wildlife professionals should raise awareness of why particular control methods are preferred, highlight the damage grey squirrels cause to other valued species, and offer local communities a variety of roles which contribute to the wider goal of native species conservation.